2014
DOI: 10.1371/journal.pone.0094844
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific and General Cognitive Effects in Chiari Malformation Type I

Abstract: ObjectiveOur objective was to use episodic memory and executive function tests to determine whether or not Chiari Malformation Type I (CM) patients experience cognitive dysfunction.BackgroundCM is a neurological syndrome in which the cerebellum descends into the cervical spine causing neural compression, severe headaches, neck pain, and number of other physical symptoms. While primarily a disorder of the cervico-medullary junction, both clinicians and researchers have suspected deficits in higher-level cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 4 publications
1
34
1
11
Order By: Relevance
“…The authors hypothesized that CM1 patients may have abnormal cerebellar white matter development and myelin integrity, leading to cognitive impairments. More recently, Allen et al [15] compared 24 adults with CM1 who had undergone decompression surgery with 24 age- and education-matched controls in several tasks of memory and executive function. Participants with CM1 performed significantly worse, when compared to control subjects, on tasks involving response inhibition, even after controlling for depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that CM1 patients may have abnormal cerebellar white matter development and myelin integrity, leading to cognitive impairments. More recently, Allen et al [15] compared 24 adults with CM1 who had undergone decompression surgery with 24 age- and education-matched controls in several tasks of memory and executive function. Participants with CM1 performed significantly worse, when compared to control subjects, on tasks involving response inhibition, even after controlling for depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…La muestra total incluyó un total de 862 sujetos, divididos en dos grupos con edades entre los 5 y 74 años. El grupo clínico se compuso por 799 participantes diagnosticados con MC-I y el grupo control por 63 controles sanos, emparejados por edad y años de educación (Allen et al, 2014;García et al, 2018). En este sentido, cabe destacar que varios estudios se caracterizaron por la ausencia de grupo control Novegno et al, 2008Lacy et al, 2011 y que un estudio contribuyó con 638 casos de pacientes diagnosticados con MC-I.…”
Section: Resultsunclassified
“…Por otro lado, cabe mencionar que 664 pacientes diagnosticados con MC-I se habían sometido a cirugía de descomprensión (Allen et al, 2014;Allen et al, 2017;Riva et al, 2011). En contraposición, 49 sujetos no fueron sometidos a intervención quirúrgica (García et al, 2018;Novegno et al, 2008).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Moreover, the hypothesis that decompressive Chiari surgery may cause or exacerbate comorbid psychiatric illness is of surgical interest. In an adult sample, Allen et al [30] suggested that neurocognitive symptoms might be attributed to surgical insult associated with decompression injury. However, psychiatric indicators such as depression or anxiety were not noted.…”
Section: Discussionmentioning
confidence: 99%